(untitled) (Journal of Pharmaceutical Negative Results, 2022)
BACKGROUND- An apical seal is one which forms a barrier between the root canal and periapex. A three-dimesional seal is created by use of Gutta Percha and an endodontic sealer, which will fill the discrepancies between the core material and dentinal walls. Since years Gutta Percha has played a versatile role in root canal obturation; but newer materials have been introduced to overcome the hydrophobic nature of it. One such material is C-Point, a premade obturation point, which absorbs residual moisture (hydrophilic nature) from the canals and expands laterally to conform to canal complexities.MATERIALS AND METHOD- Fifteen freshly extracted mandibular incisors were prepared with Protaper Universal rotary files, and obturated by dividing into three groups of 5 teeth each. Group I- Gutta-percha & AH-Plus, Group II, Gutta-percha & Nanoseal S, and Group III C-point & BioRoot RCS. After coating the teeth with nail polish except the apical 2 mm, they were suspended in methylene blue dye for 12 hour. They were then sectioned longitudinally and observed under stereomicroscope for the linear dye penetration. All the groups were compared by using ONE WAY ANOVA.RESULTS- One way ANOVA showed Group I with minimum microleakage (Mean ± SD) of 3.29±1.32 μm, followed by Group II 4.25±1.83 μm and Group III with maximum micro-leakage 5.53±1.72 μm.CONCLUSION- Gutta percha when used with AH-Plus showed better sealing ability as compared to Gutta Percha and Nanoseal S. The newer material, C-Point with BioRoot RCS showed the least sealing ability.